A new species of an unexplored diatom genus: Gomphosphenia minima sp. nov. (Cymbellales, Rhoicospheniaceae) - González-Paz, Lorena; Almeida, Salomé F.p.; Blanco, Saúl; Delgado, Cristina (Phytotaxa, 2022)
Gomphosphenia minima sp. nov. is a new freshwater diatom described from central Portugal,  found in samples from a mountain stream. The species is described here based on light and scanning electron microscopy. This taxon is compared with other Gomphosphenia taxa such as G. fontinalis, G. lingulatiformis and G. tackei. Gomphosphenia minima sp. nov. is characterized by clavate to linear-lanceolate valves with rounded apices and a wide axial area not clearly separated from the central area. This taxon can be confused with G. fontinalis in terms of length and the shape of the central and axial area but they can be easily differentiated because the new species is narrower and the stria density is lower. The new species was found in low abundance in February 2012 and the stream had low electric conductivity levels, neutral pH values, low water temperature and low nutrient content.